1992
DOI: 10.1111/j.1432-1033.1992.tb17491.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of actin on the tryptic digestion of myosin subfragment 1 in the weakly attached state

Abstract: The structure of myosin subfragment 1 (SI) in the weakly attached complex with actin was studied at three specific sites, at the 50-kDa/20-kDa and 27-kDa/SO-kDa junctions, and at the N-terminal region, using tryptic digestion as a structure-exploring tool. The structure of S1 at the vicinity of the 50-kDa/20-kDa junction is pH dependent in the weakly attached state because the tryptic cleavage at this site was fully protected by actin at pH 6.2, but the protection was only partial at pH 8.0. Since the actin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It seems more likely that a long-distance communication pathway exists between these sites. In favor of this suggestion are literature data showing that F-actin suppresses the N-terminal tryptic cleavage of S1 both in the strongly attached state [26] and in the weakly attached state [27]. The cleavage between Arg23 and Ile24 probably disrupts this communication pathway, thus preventing the global conformational changes in the myosin head induced by actin binding to loop 2.…”
Section: N-terminal Cleavage Dramatically Decreases the Thermal Stabimentioning
confidence: 99%
See 2 more Smart Citations
“…It seems more likely that a long-distance communication pathway exists between these sites. In favor of this suggestion are literature data showing that F-actin suppresses the N-terminal tryptic cleavage of S1 both in the strongly attached state [26] and in the weakly attached state [27]. The cleavage between Arg23 and Ile24 probably disrupts this communication pathway, thus preventing the global conformational changes in the myosin head induced by actin binding to loop 2.…”
Section: N-terminal Cleavage Dramatically Decreases the Thermal Stabimentioning
confidence: 99%
“…Examination of the S1 structure has suggested that there are contacts between the essential light chain in the regulatory domain and some parts of the heavy chain in the motor domain [45]. Essential light-chain residues 103-115 form a helix and lie in close proximity to a helix-loop motif near the N-terminus of the heavy chain (residues [21][22][23][24][25][26][27][28][29][30][31]. This contact may serve as an additional communication pathway between the motor domain and the regulatory domain, and it may play a crucial role in the transmission of actin-induced conformational changes from loop 2 to the regulatory domain through the motor domain.…”
Section: N-terminal Cleavage Dramatically Decreases the Thermal Stabimentioning
confidence: 99%
See 1 more Smart Citation